Optimization of temperature parameters for the autothermic pyrolysis in-situ conversion process of oil shale. (1st February 2023) - Xu, Shaotao; Lü, Xiaoshu; Sun, Youhong; Guo, Wei; Li, Qiang; Liu, Lang; Kang, Shijie; Deng, Sunhua
Abstract: In this study, a temperature optimization strategy for the Huadian oil shale autothermal pyrolysis in-situ conversion process (ATS) was first proposed by systematically investigating the reaction characteristics of various semi-cokes. As the pyrolysis temperature rised, the semi-coke's calorific value was found to undergo three different stages of increasing, decreasing, and flattening, peaking at around 330 °C. Additionally, the semi-cokes formed at different temperatures exhibited similar combustion characteristics, including combustion activation energy, combustion characteristic parameters, and product release characteristics. Due to the serious pore blockage caused by the substantial generation and the ignition coking of the bitumen, the reaction characteristics of semi-cokes were dramatically decreased at about 330 °C. Finally, the relationship between in-situ heat generation and demand at various stages of ATS process was discussed, and a reasonable strategy for the screening of temperature parameters was proposed. According to this strategy, the optimal control temperature for the preheating stage was determined at 350–370 °C and at T act (defined in 4.3.2) for the retorting zone in the reaction stage. The results of this study provide a new perspective on the theoretical foundation of the ATS process and have crucial guiding implications for practical engineering applications. Highlights: The oil shale semi-coke obtained at 330 °C shows the highest calorific value. The combustion properties of semi-coke obtained at 330 °C are greatly reduced. The ATS process is theoretically viable even at lower heat utilization rates. The optimal preheating temperature for Huadian oil shale ATS process is 350–370 °C. The preferred maximum temperature for the pyrolysis zone in ATS is the defined T act .